Preface - Kumar, M. Vishu; Salma, A.; Hanumagowda, B. N.; Kumar, U. Vijaya Chandra (Communications in Mathematics and Applications, 2023)
It is a great privilege for us to present the proceedings of the Third International Conference on Recent Trends in Applied and Computational Mathematics (ICRTACM-2022), held at Department of Mathematics, School of Applied Sciences, REVA University, Bangalore, India during 10th and 11th October 2022 as a special issue entitled “Recent Trends in Applied and Computational Mathematics” in the Communications in Mathematics and Applications. We hope that you will find it useful, exciting and inspiring.Mathematics is an ever-evolving field, with applications that extend across multiple disciplines, from engineering and physics to economics and computer science. The synergy between applied and computational mathematics has paved the way for numerousbreakthroughs and innovations. This conference served as a platform for researchers from academic and industry to present their original work and exchange ideas, information, techniques, and applications in the field of Applied and Computational Mathematics. The papers included in these proceedings reflect the diversity and depth of mathematical research showcased during the conference. They delve into a wide spectrum of topics, from abstract theories to real-world problem-solving. The research presented here is a testament to the collective efforts of mathematicians who are pushing the boundaries of human understanding.We would like to extend our heartfelt gratitude to all the participants, authors, reviewers, and organizers who contributed to the success of this conference. Your dedication and passion for mathematics have been instrumental in creating a vibrant and stimulating environment for intellectual exchange.We hope that these proceedings serve as a valuable resource for researchers, students, and enthusiasts alike, inspiring further exploration and collaboration in the fascinating world of mathematics.We also record our thanks to RGN Publications and its editorial staff for their sincere cooperation in the publication of this proceedings.